Are Malaysian undergraduates ‘digital natives’ in the true sense of the word? a quantitative analysis - Thang, Siew Ming; Nurjanah Mohd Jaafar,; Radha Nambiar,; Zaini Amir,; Wong, Fook Fei (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
This generation of students, born between 1980 and 1994, has grown up with technology from a very young age. They are hypothesized to possess sophisticated knowledge and skills in Information Communication Technologies (ICT) and are highly motivated to learn digitally. This implies a need to change the knowledge content and methods of delivery in universities to cater to their needs. However, many studies have revealed that the ‘digital natives’ use of technology is neither extensive nor diverse. No substantial studies have been undertaken in Malaysia to support or refute such claims. This study, undertaken at a Malaysian public university, used a questionnaire to investigate students’ patterns and perceptions of ICT use for learning English. The findings revealed that even though students’ reception towards use of technology was very positive, there was a lack in diversity and sophistication. It further proposed that cultural factor is an influencing factor.